UJI KELURUSAN MESIN RESONANCE 63 KN DENGAN COUPON TEST PESAWAT N219 MENGGUNAKAN STRAIN GAUGE - Koswara .; Syaiful Arif (Institut Sains dan Teknologi Nasional, 2022)
ABSTRACT ABSTRACT This study aims to determine the capacity of the resonance machine capacity 63 kn which has the influence of strain in analyzing the static loading stress on the coupon test. The study used a coupon test specimen with a predetermined dimension, using eight strain gauges in a vertical direction, where the response of the strain gauge system was fast enough to sense dynamic strain with a frequency greater than 100 kHz. The strain gauge used was a strain gauge for gauge bridges where the application is easy. The results obtained show that there is no strain and stress on specimens that point to numbers below -100 to 100, but this number is considered good because it does not exceed the number specified in the tolerance category the third step measurement results are used for knowing the ability to reset, relative error and machine linearity and the expected deviation value is not more than 1%. Keywords: resonance machine, coupon test, strain gauge, specimen